Primary Peritoneal Carcinosarcoma: A Case Report - Erz, Logan; Smith, Brandon; Larson, Brandon; Ma, Truong (Frontiers in Surgery, 2021)
Introduction: Carcinosarcoma, also known as malignant mixed Mullerian tumor (MMMT) is a malignant biphasic neoplasm consisting of carcinomatous and malignant non-epithelial components of mesenchymal origin. MMMTs typically arise from the female genital tract in patients over 40 years old. Primary extragenital MMMTs are extremely rare with published literature totaling 40 reported cases. The primary peritoneal carcinosarcoma is an aggressive tumor as patients with this tumor have an average survival of 7.6 months. Surgical debulking is the mainstay of treatment for these tumors and systemic chemotherapy is advised in all cases. Case: A 48-year-old Amish female presented with 5 day history of bloating and abdominal pain superimposed on a 1 year history of worsening fatigue and intermittent bloody bowel movements. She was found to have a pelvic mass on physical exam. Computed tomography scan of the abdomen and pelvis that demonstrated stricturing of the sigmoid colon, and a large multi-cystic mass in the midline pelvis measuring 12.5 × 9.9 × 11.7 cm. Colonoscopy showed stenosis due to external compression without intraluminal lesion. CEA and CA 125 levels were elevated and CA 19-9 was normal. Exploratory laparotomy was performed with en-bloc resection of a 15 cm mass originating from the sigmoid colon mesentery with several other small tumor deposits throughout the mesentery. Pathology diagnosed primary peritoneal carcinosarcoma Mullerian-type with three positive lymph nodes. Conclusion: Malignant mixed Mullerian tumor (carcinosarcoma) caries a universally grim prognosis. Herein, we report a unique case of primary peritoneal carcinosarcoma and discuss the work-up and surgical management of this rare tumor.